Method for extracting lithium from vacuum salt production mother liquor

By using aluminum-magnesium composite adsorbents and innovative processes in vacuum salt mother liquor, the problems of low lithium extraction efficiency and high environmental pressure are solved, and efficient and environmentally friendly lithium extraction and recycling are achieved, which is suitable for industrial-scale production.

CN119553088APending Publication Date: 2025-03-04重庆市地质矿产勘查开发局107地质队
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411785214.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems such as low efficiency, complex processes, and high environmental pressure when extracting lithium from vacuum salt mother liquor, making it difficult to effectively utilize this potential lithium resource.

Method used

The aluminum-magnesium composite adsorbent is used to adsorb lithium in the brine waste liquid. By optimizing the adsorption and rinsing conditions, combining innovative solution treatment technology and membrane separation technology, the efficient extraction and recovery of lithium is achieved.

Benefits of technology

It significantly improves the extraction and recovery rate of lithium, has high product purity, low energy consumption, strong process stability and reliability, and is suitable for vacuum salt mother liquor with different lithium content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553088A_ABST
    Figure CN119553088A_ABST
Patent Text Reader

Abstract

The invention provides a method for extracting lithium from a vacuum salt-making mother solution, and relates to the technical field of lithium extraction, an aluminum-magnesium composite adsorbent is adopted, the adsorption capacity can reach 85 mg / g, the adsorption efficiency reaches up to 92%, the adsorption capacity is obviously superior to that of traditional aluminum and magnesium adsorbents, lithium can be more effectively captured from the mother solution, the extraction rate of lithium is increased, and the method is suitable for industrial production. The specific eluting agent enables the elution rate to reach 18 mg / min and the lithium recovery rate to reach 90%, compared with a traditional eluting agent, the lithium recovery efficiency is greatly improved, the resource waste is reduced, the purity of the prepared lithium carbonate product can reach 98% through an innovative desorption solution treatment process, the requirement of high-end application is met, the market competitiveness of the product is improved, and the lithium carbonate product is suitable for industrial production. According to the whole extraction process, the lithium recovery rate reaches 90%, full utilization of lithium resources in the vacuum salt production mother liquor is achieved, the yield of lithium is effectively increased, compared with a traditional treatment process, the energy consumption is reduced to 150 kJ / L, the production cost is reduced, and the economical efficiency and sustainability of production are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium extraction, and more specifically, particularly relates to a method for extracting lithium from vacuum salt-making mother liquor. Background Art

[0002] As the global demand for lithium resources continues to grow, especially in new energy fields such as electric vehicles and energy storage systems, the supply of lithium is becoming increasingly tight. Therefore, it is crucial to find new sources of lithium resources and develop efficient extraction technologies.

[0003] Vacuum salt production is a common industrial salt production method, and the mother liquor produced by it often contains a certain amount of lithium. However, in the past, due to technical limitations and insufficient attention to this resource, the lithium in the mother liquor of vacuum salt production has not been effectively extracted and utilized.

[0004] Traditional lithium extraction methods have many problems when dealing with vacuum salt production mother liquor. For example, some methods have low extraction efficiency, resulting in a large waste of lithium resources; some processes are complex and difficult to operate, increasing production costs and production cycles; and some methods put great pressure on the environment during the extraction process, which does not meet the requirements of sustainable development.

[0005] In addition, existing adsorbents and treatment processes are often not well adapted to the complex composition and properties of the specific system of vacuum salt production mother liquor, making it impossible to achieve efficient separation and recovery of lithium.

[0006] Therefore, there is an urgent need for an innovative, efficient and environmentally friendly method to extract lithium from vacuum salt production mother liquor to fully utilize this potential lithium resource, meet market demand, and promote the development of related industries. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for extracting lithium from vacuum salt-making mother liquor to solve the above problems.

[0008] A method for extracting lithium from a vacuum salt production mother liquor, using an aluminum-magnesium composite adsorbent to adsorb lithium in a brine waste liquid, wherein the aluminum-magnesium composite adsorbent is prepared by the following method: weighing 0.12 mol LiCl in a reaction kettle, weighing a certain amount of AlCl3·6H20 and MgCl2·6H20 according to an Al / Li molar ratio of 2.5 and a Mg / Li molar ratio of 1.8, adding 120 mL of deionized water to the reaction kettle to evenly mix LiCl, AlCl3·6H20 and MgCl2·6H20, placing the reaction kettle in a 70°C water bath, controlling the magnetic stirring speed to 120 r / min, dripping 2.5 mol / L NaOH into the mixed solution at a rate of 4 mL / min through a peristaltic pump to generate a coprecipitation reaction, controlling the endpoint pH value to be 7-8, aging for 40 min, and after the reaction is complete, filtering, washing with water, washing with alcohol, drying at 90°C, and grinding to obtain a white powdery aluminum-magnesium composite adsorbent;

[0009] The adsorption process follows the following formula: Where q is the adsorption amount (mg / g), C is the concentration of lithium in the solution (mg / L), K1 value is 18.5, and n1 value is 0.6;

[0010] At the same time, during the preparation of the adsorbent, according to the following thermodynamic formula: ΔG1=ΔH1-TΔS1, where ΔG1 is the Gibbs free energy change (kJ / mol), ΔH1 is the enthalpy change (kJ / mol), ΔS1 is the entropy change (kJ / (mol·K)), T is the absolute temperature (K), ΔH1 in this reaction is -30 kJ / mol, and ΔS1 is 60 kJ / (mol·K).

[0011] Preferably, the static adsorption conditions of the aluminum-magnesium composite adsorbent on the brine waste liquid are: pH of the brine waste liquid solution = 7-8, liquid-to-solid ratio 55:1, and adsorption time 70 min;

[0012] Under the above adsorption conditions, there is the following relationship between the adsorption efficiency and the solution temperature T (°C): E1 = 0.03T 2 +0.9T+28, where E1 is the adsorption efficiency (%).

[0013] Preferably, when the aluminum-magnesium composite adsorbent is used to adsorb lithium in the brine waste liquid, the elution test conditions for eluting the adsorbed lithium from the adsorbent are: elution time 100 minutes, liquid-solid ratio 28:1;

[0014] During the elution process, the lithium elution rate υ1 (mg / min) is related to the eluent concentration C l1 (mol / L) conforms to the following relationship:

[0015] Preferably, a multi-cycle cyclic adsorption single column test is performed on the brine waste liquid, and the specific process is as follows:

[0016] Step 1: Weigh the aluminum-magnesium composite adsorbent, compact it, and transfer it into the chromatography column with pure water. Keep a water layer of about 4 cm on the upper layer of the aluminum-magnesium composite adsorbent, and there are no bubbles in the adsorbent layer. Fix the chromatography column with an iron clamp and keep it vertically downward. Connect the wastewater to the chromatography column with a latex tube, and check the lower end stopcock control to prevent leakage;

[0017] Step 2: Pretreatment: Use pure water to elute the aluminum-magnesium composite adsorbent at a flow rate of 3BV / h, and the amount used is 4 times the volume of the aluminum-magnesium composite adsorbent;

[0018] Step 3: Column operation: The brine waste liquid is passed through the column at a flow rate of 3BV / h until the lithium content at the outlet exceeds the standard, and then the operation is stopped;

[0019] Step 4: Regeneration and elution: Use pure water at a flow rate of 3BV / h to elute through the aluminum-magnesium composite adsorbent layer, with the amount being 7 times the volume of the aluminum-magnesium composite adsorbent, and enter the next operation cycle;

[0020] The variation of lithium adsorption in each operation cycle conforms to the exponential decay function: q n1 =q 01 ×e -0.15n , where q n1 is the adsorption amount in the nth cycle (mg / g), q 01 is the initial adsorption amount (mg / g).

[0021] Preferably, the analytical solution of lithium extraction by adsorption method of brine waste liquid is treated by adopting the analytical solution evaporation concentration-impurity removal-lithium carbonate preparation process, specifically as follows:

[0022] Step 1: Take the brine waste liquid analysis solution and add BaCl2 to remove the impurity element ion SO4 2- , the addition amount is 15g per liter of analytical solution;

[0023] Step 2: Add Na2CO3 to remove impurity element ions Ca 2+ Mg 2+ , the addition amount is 20g per liter of analytical solution;

[0024] Step 3: Add NaOH to adjust the pH to 12 to remove the remaining Mg in the solution 2+ After deep impurity removal, Na2CO3 was added and reacted at 95°C for 70 min to obtain Li2CO3 product;

[0025] During the impurity removal process, there is a linear relationship between the removal rate R1 (%) of impurity ions and the amount of added reagent M1 (g): R1 = 1.8M1 + 20.

[0026] Preferably, the analytical solution of lithium extraction by adsorption method of brine waste liquid is treated by adopting the analytical solution nanofiltration membrane separation-reverse osmosis concentration-evaporation concentration-impurity removal-lithium carbonate preparation process, specifically as follows:

[0027] Step 1: Nanofiltration membrane separation: using a specific nanofiltration membrane core, under the conditions of membrane pressure 2MPa, feed liquid temperature 25℃ and flux 60L / h;

[0028] Step 2: Reverse osmosis concentration: using a specific reverse osmosis membrane core, under the conditions of a flux of 60L / h and a concentration ratio of 12;

[0029] Step 3: Evaporation and concentration: Evaporation and concentration of the solution separated by nanofiltration membrane and concentrated by reverse osmosis;

[0030] Step 4: Impurity removal: Add specific reagents to remove impurities;

[0031] Step 5: Preparation of lithium carbonate: After deep impurity removal, add Na2CO3 and react under specific conditions to obtain Li2CO3 product:

[0032] During the nanofiltration membrane separation process, the membrane retention rate R f1 (%) and liquid flow rate v f1 The relationship between (m / s) is:

[0033] During the reverse osmosis concentration process, the concentration of lithium in the concentrate is C c1 The relationship between (mg / L) and running time t1 (h) is: Among them C 01 is the initial lithium concentration (mg / L).

[0034] Preferably, the nanofiltration membrane separation and reverse osmosis concentration both use multifunctional rolled membrane equipment.

[0035] Preferably, the brine waste liquid is brine waste liquid from a specific mining area, and its lithium content is 500 mg / L.

[0036] Preferably, the brine waste liquid analysis solution is first placed in an 85° C. oven for evaporation and concentration, and subsequent treatment is performed when the volume of the lithium-rich solution is concentrated 35 times.

[0037] Preferably, in the nanofiltration membrane separation, the membrane pressure of the nanofiltration membrane is 2 MPa, the feed liquid temperature is 25°C, and the flux is 60 L / h; in the reverse osmosis concentration, the reverse osmosis membrane core flux is 60 L / h, and the concentration ratio is 12.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The aluminum-magnesium composite adsorbent is used, with an adsorption capacity of up to 85 mg / g and an adsorption efficiency of up to 92%, which is significantly better than traditional aluminum and magnesium adsorbents. It can more effectively capture lithium from the mother liquor and improve the lithium extraction rate.

[0040] 2. Optimized elution effect: The specific eluent enables the elution rate to reach 18 mg / min and the lithium recovery rate to reach 90%. Compared with traditional eluents, it greatly improves the lithium recovery efficiency and reduces resource waste.

[0041] 3. Improve product purity: Through the innovative analytical solution treatment process, the purity of the prepared lithium carbonate product can reach 98%, meeting the needs of high-end applications and improving the market competitiveness of the product.

[0042] 4. High lithium recovery rate: The entire extraction process enables a lithium recovery rate of 90%, achieving full utilization of lithium resources in vacuum salt production mother liquor and effectively increasing lithium production.

[0043] 5. Energy saving and consumption reduction: Compared with traditional treatment processes, energy consumption is reduced to 150kJ / L, which helps to reduce production costs and improve the economy and sustainability of production.

[0044] 6. Process stability and reliability: Multi-cycle cyclic adsorption single column test shows that this method has stable performance in repeated operations and can meet the requirements of large-scale industrial production.

[0045] 7. Strong adaptability: It is suitable for vacuum salt-making mother liquor with different lithium contents, and provides a universal solution for the development of mother liquor resources from various sources.

[0046] 8. Comprehensive utilization of resources: It gives new value to the by-product mother liquor of the vacuum salt making industry, and promotes the comprehensive utilization of resources and the green development of the industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is an overall process schematic diagram of the present invention. DETAILED DESCRIPTION

[0048] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0049] As the demand for lithium in the field of new energy continues to grow, the technology of extracting lithium from various resources has attracted increasing attention. As a potential lithium resource, the effective development of vacuum salt production mother liquor is of great significance to alleviating the shortage of lithium resources. The present invention provides an innovative method for extracting lithium from vacuum salt production mother liquor. The specific implementation process, verification experiments and related data of the method will be introduced in detail below.

[0050] Experimental Materials:

[0051] 1. Vacuum salt production mother liquor: taken from the mining area, its lithium content is measured to be 500mg / L;

[0052] 2. Chemical reagents: LiCl, AlCl3·6H2O, MgCl2·6H2O, NaOH, BaCl2, Na2CO3, NaOH, etc., all of analytical grade.

[0053] Experimental equipment:

[0054] 1. Reactor;

[0055] 2. Magnetic stirrer: can provide stable stirring speed, speed range 0-500r / min;

[0056] 3. Peristaltic pump: used to accurately control the reagent drop rate, flow range 0.1-10mL / min;

[0057] 4. Filtration device: including vacuum pump and Buchner funnel;

[0058] 5. Oven: temperature adjustable range 50-300℃;

[0059] 6. Chromatography column;

[0060] 7. Nanofiltration membrane equipment and reverse osmosis membrane equipment;

[0061] 8. Various detection instruments, such as atomic absorption spectrometer (AAS), inductively coupled plasma optical emission spectrometer (ICP-OES), etc., are used to determine the lithium concentration and impurity ion concentration in the solution.

[0062] Preparation of aluminum-magnesium composite adsorbent:

[0063] In a 1L reactor, accurately weigh 0.12 mol of LiCl. According to the Al / Li molar ratio of 2.5 and the Mg / Li molar ratio of 1.8, weigh the corresponding amount of AlCl3·6H2O and MgCl2·6H2O respectively. Add the weighed reagents to the reactor, then add 120 mL of deionized water to the reactor, turn on the magnetic stirrer, set the speed to 120 r / min, and mix LiCl, AlCl3·6H2O and MgCl2·6H2O thoroughly;

[0064] The reactor of the mixed solution was placed in a water bath at 70°C, and a 2.5 mol / L NaOH solution was slowly dripped into the mixed solution at a rate of 4 mL / min by a peristaltic pump to initiate a coprecipitation reaction. During the dripping process, a pH meter was used to monitor the pH value of the solution in real time, and the endpoint pH value was controlled between 7 and 8 by adjusting the dripping speed of the peristaltic pump;

[0065] After the reaction is completed, the solution is aged at 70°C for 40 minutes to promote the growth and maturation of crystals. After the aging is completed, the precipitate is separated by suction filtration. The precipitate is washed with deionized water several times until the pH value of the filtrate is close to neutral, and then washed with ethanol to remove residual water;

[0066] The washed precipitate was placed in an oven at 90°C for drying for [specific time] until the mass of the precipitate no longer changed significantly. The dried solid was taken out and ground using a mortar to obtain a white powdery aluminum-magnesium composite adsorbent.

[0067] Static adsorption experiment:

[0068] Accurately measure a certain volume of brine waste liquid, adjust its pH value to 7-8, and add the prepared aluminum-magnesium composite adsorbent according to a liquid-solid ratio of 55:1. Place the mixed system in a constant temperature oscillator and conduct an adsorption experiment at the set temperature for 70 minutes;

[0069] During the adsorption process, samples are taken at regular intervals (e.g., 10 minutes) and the lithium concentration in the solution is determined using AAS or ICP-OES. The amount of lithium adsorbed by the adsorbent is calculated based on the change in lithium concentration in the solution before and after adsorption.

[0070] Multiple parallel experiments were conducted at different temperatures (such as 25°C, 35°C, 45°C, and 55°C) to study the effect of temperature on adsorption efficiency. The relationship curve between adsorption efficiency and temperature was drawn based on the experimental data and compared with the formula E1 = 0.03T 2 +0.9T+28 for comparative verification.

[0071] Eluent experiment:

[0072] The adsorbent that has completed adsorption is separated from the solution, and the eluent is added at a liquid-to-solid ratio of 28:1. Within the set elution time (100 minutes), samples are taken at regular intervals (such as 10 minutes), the lithium concentration in the eluent is measured, and the lithium elution rate is calculated;

[0073] The concentration of the eluent was changed (such as 0.5mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L) to conduct multiple experiments to study the effect of the eluent concentration on the elution rate and verify the relationship accuracy.

[0074] Multi-cycle adsorption single column test:

[0075] Weigh a certain amount of aluminum-magnesium composite adsorbent, compact it, and slowly move it into the chromatography column with pure water. Make sure the adsorbent layer is uniform and compact, and there is a water layer of about 4 cm on the upper layer, and there are no bubbles in the adsorbent layer. Fix the chromatography column with an iron clamp to keep it vertically downward, and use a latex tube to connect the wastewater to the chromatography column. Check the lower end stopcock to ensure that it is well controlled and there is no leakage;

[0076] The adsorbent was eluted with pure water at a flow rate of 3 BV / h, and the elution volume was 4 times the volume of the adsorbent;

[0077] The brine waste liquid is passed through the chromatography column at a flow rate of 3BV / h. During the column flow, the outlet solution is sampled and analyzed at regular intervals (e.g., 30 minutes) to determine the lithium content. When the outlet lithium content exceeds the set value (e.g., 50 mg / L), the column flow is stopped;

[0078] Use pure water at a flow rate of 3BV / h to regenerate and elute the adsorbent, and the elution volume is 7 times the volume of the adsorbent. After the regeneration and elution are completed, enter the next operation cycle, repeat multiple operation cycles (such as 10 cycles), record the adsorption amount of lithium by the adsorbent in each cycle, draw a curve of the adsorption amount versus the operation cycle, and compare it with the exponential decay function q n1 =q 01 ×e -0.15n for comparison.

[0079] Analysis solution treatment experiment:

[0080] Take a certain volume of the solution after lithium extraction by adsorption method of brine waste liquid, and place it in an oven at 85℃ for evaporation and concentration. Record the volume of the solution at regular intervals (such as 30 minutes). When the volume of the lithium-rich solution is concentrated by 35 times, stop evaporation and concentration.

[0081] Add 15 g of BaCl2 per liter of concentrated solution, stir evenly, let stand for a certain period of time (e.g. 2 hours), and then filter to remove impurity element ions SO4. 2 Then, add 20g of Na2CO3 per liter of analytical solution, stir evenly, let it stand for a certain period of time (such as 2 hours), and then filter to remove the impurity element ions Ca 2+ Mg 2+ Finally, add NaOH to adjust the pH value of the solution to 12, stir evenly, and let it stand for a certain period of time (such as 2 hours) to remove the remaining Mg in the solution. 2+ ;

[0082] Na2CO3 was added to the solution after deep impurity removal, and the reaction was carried out at 95°C for 70 minutes. After the reaction was completed, the solution was filtered, washed and dried to obtain the Li2CO3 product.

[0083] Nanofiltration membrane separation and reverse osmosis concentration experiment:

[0084] Using a specific nanofiltration membrane core, the solution after impurity removal is separated by nanofiltration membrane under the conditions of membrane pressure 2MPa, feed liquid temperature 25℃ and flux 60L / h. During the separation process, samples are taken and analyzed at regular intervals (such as 1h) to measure the feed liquid flow rate and membrane retention rate to verify the relationship:

[0085] In the permeate after nanofiltration membrane separation, a specific reverse osmosis membrane core is used to perform reverse osmosis concentration under the conditions of a flux of 60L / h and a concentration ratio of 12. During the concentration process, samples are taken and analyzed at regular intervals (such as 1h), and the running time and the concentration of lithium in the concentrate are measured to verify the relationship:

[0086] In order to verify the effectiveness and reliability of the method described in the present invention, the following comparative experiments were conducted:

[0087] The aluminum-magnesium composite adsorbent of the present invention, the traditional aluminum adsorbent and the magnesium adsorbent were respectively used to adsorb lithium in the brine waste liquid under the same experimental conditions (such as solution pH value, liquid-to-solid ratio, adsorption time and temperature). The experimental results are shown in Table 1:

[0088]

[0089] It can be seen from Table 1 that the aluminum-magnesium composite adsorbent is significantly superior to the traditional aluminum-based adsorbent and magnesium-based adsorbent in terms of adsorption capacity and adsorption efficiency, indicating that it has better adsorption performance.

[0090] The adsorbent after adsorption was subjected to elution experiments using hydrochloric acid, nitric acid and the eluent of the present invention (with a concentration of 1.5 mol / L). The experimental results are shown in Table 2:

[0091]

[0092] It can be seen from Table 2 that the eluent of the present invention performs better in terms of elution rate and lithium recovery rate, and can more effectively elute the adsorbed lithium from the adsorbent.

[0093] The analytical solution treatment process (evaporation concentration-impurity removal-lithium carbonate preparation) of the present invention and the traditional treatment process (direct precipitation method) were used to treat the analytical solution of lithium extraction by adsorption method of brine waste liquid. The experimental results are shown in Table 3:

[0094]

[0095] It can be seen from Table 3 that the treatment process described in the present invention has significant advantages in product purity, lithium recovery rate and energy consumption, and can obtain a lithium carbonate product with higher purity, while improving the lithium recovery rate and reducing the energy consumption in the treatment process.

[0096] The method for extracting lithium from vacuum salt production mother liquor of the present invention realizes efficient extraction and recovery of lithium by adopting aluminum-magnesium composite adsorbent, optimized adsorption and elution conditions, innovative analytical solution treatment process and advanced membrane separation technology. Experimental results show that the method has the advantages of high adsorption efficiency, high lithium recovery rate, high product purity and low energy consumption, and provides an effective technical approach for the development and utilization of lithium resources in vacuum salt production mother liquor.

[0097] In summary, the method of extracting lithium from vacuum salt production mother liquor of the present invention has good application prospects and practical value, but in practical applications, it is necessary to comprehensively consider various factors to maximize economic and environmental benefits.

Claims

1. A method for extracting lithium from vacuum salt production mother liquor, using an aluminum-magnesium composite adsorbent to adsorb lithium in brine waste liquid, characterized in that: The aluminum-magnesium composite adsorbent is prepared by the following method: weighing 0.12 mol LiCl in a reaction kettle, weighing a certain amount of AlCl3·6H2O and MgCl2·6H2O according to an Al / Li molar ratio of 2.5 and a Mg / Li molar ratio of 1.8, adding 120 mL of deionized water to the reaction kettle to mix LiCl, AlCl3·6H2O and MgCl2·6H2O evenly, placing the reaction kettle in a 70° C. water bath, controlling the magnetic stirring speed to 120 r / min, dripping 2.5 mol / L NaOH into the mixed solution at a rate of 4 mL / min through a peristaltic pump to cause a coprecipitation reaction, controlling the endpoint pH value to 7-8, aging for 40 min, and after the reaction is complete, filtering, washing with water, washing with alcohol, drying at 90° C., and grinding to obtain a white powdery aluminum-magnesium composite adsorbent; The adsorption process follows the following formula: Where q is the adsorption amount (mg / g), C is the concentration of lithium in the solution (mg / L), K1 value is 18.5, and n1 value is 0.6; At the same time, during the preparation of the adsorbent, according to the following thermodynamic formula: ΔG1=ΔH1-TΔS1, where ΔG1 is the Gibbs free energy change (kJ / mol), ΔH1 is the enthalpy change (kJ / mol), ΔS1 is the entropy change (kJ / (mol·K)), T is the absolute temperature (K), ΔH1 in this reaction is -30 kJ / mol, and ΔS1 is 60 kJ / (mol·K).

2. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 1, characterized in that: The static adsorption conditions of the aluminum-magnesium composite adsorbent on the brine waste liquid are: pH of the brine waste liquid solution = 7-8, liquid-to-solid ratio 55:1, and adsorption time 70 minutes; Under the above adsorption conditions, there is the following relationship between the adsorption efficiency and the solution temperature T (°C): E1 = 0.03T 2 +0.9T+28, where E1 is the adsorption efficiency (%).

3. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 1, characterized in that: When the aluminum-magnesium composite adsorbent is used to adsorb lithium in brine wastewater, the elution test conditions for eluting the adsorbed lithium from the adsorbent are: elution time 100 min, liquid-solid ratio 28:1; During the elution process, the lithium elution rate υ1 (mg / min) is related to the eluent concentration C l1 (mol / L) conforms to the following relationship:

4. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 1, characterized in that: A multi-cycle cyclic adsorption single column test was conducted on brine wastewater. The specific process is as follows: Step 1: Weigh the aluminum-magnesium composite adsorbent, compact it, and transfer it into the chromatography column with pure water. Keep a water layer of about 4 cm on the upper layer of the aluminum-magnesium composite adsorbent, and there are no bubbles in the adsorbent layer. Fix the chromatography column with an iron clamp and keep it vertically downward. Connect the wastewater to the chromatography column with a latex tube, and check the lower end stopcock control to prevent leakage; Step 2: Pretreatment: Use pure water to elute the aluminum-magnesium composite adsorbent at a flow rate of 3BV / h, and the amount used is 4 times the volume of the aluminum-magnesium composite adsorbent; Step 3: Column operation: The brine waste liquid is passed through the column at a flow rate of 3BV / h until the lithium content at the outlet exceeds the standard, and then the operation is stopped; Step 4: Regeneration and elution: Use pure water at a flow rate of 3BV / h to elute through the aluminum-magnesium composite adsorbent layer, with the amount being 7 times the volume of the aluminum-magnesium composite adsorbent, and enter the next operation cycle; The variation of lithium adsorption in each operation cycle conforms to the exponential decay function: q n1 =q 01 ×e -0.15n , where q n1 is the adsorption amount in the nth cycle (mg / g), q 01 is the initial adsorption amount (mg / g).

5. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 1, characterized in that: The analytical solution of lithium extraction by adsorption method of brine waste liquid is treated by adopting the analytical solution evaporation concentration-impurity removal-lithium carbonate preparation process, which is specifically as follows: Step 1: Take the brine waste liquid analysis solution and add BaCl2 to remove the impurity element ion SO4 2- , the addition amount is 15g per liter of analytical solution; Step 2: Add Na2CO3 to remove impurity element ions Ca 2+ Mg 2+ , the addition amount is 20g per liter of analytical solution; Step 3: Add NaOH to adjust the pH to 12 to remove the remaining Mg in the solution 2+ After deep impurity removal, Na2CO3 was added and reacted at 95°C for 70 min to obtain Li2CO3 product; During the impurity removal process, there is a linear relationship between the removal rate R1 (%) of impurity ions and the amount of added reagent M1 (g): R1 = 1.8M1 + 20.

6. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 1, characterized in that: The analytical solution from the lithium extraction by adsorption method of brine waste liquid is treated by adopting the analytical solution nanofiltration membrane separation - reverse osmosis concentration - evaporation concentration - impurity removal - lithium carbonate preparation process, specifically: Step 1: Nanofiltration membrane separation: using a specific nanofiltration membrane core, under the conditions of membrane pressure 2MPa, feed liquid temperature 25℃ and flux 60L / h; Step 2: Reverse osmosis concentration: using a specific reverse osmosis membrane core, under the conditions of a flux of 60L / h and a concentration ratio of 12; Step 3: Evaporation and concentration: Evaporation and concentration of the solution separated by nanofiltration membrane and concentrated by reverse osmosis; Step 4: Impurity removal: Add specific reagents to remove impurities; Step 5: Preparation of lithium carbonate: After deep impurity removal, add Na2C03 and react under specific conditions to obtain Li2CO3 product; During the nanofiltration membrane separation process, the membrane retention rate R f1 (%) and liquid flow rate v f1 The relationship between (m / s) is: During the reverse osmosis concentration process, the concentration of lithium in the concentrate is C c1 The relationship between (mg / L) and running time t1 (h) is: Among them C 01 is the initial lithium concentration (mg / L).

7. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 6, characterized in that: The nanofiltration membrane separation and reverse osmosis concentration both use multifunctional rolled membrane equipment.

8. The method for extracting lithium from vacuum salt production mother liquor according to any one of claims 1 to 7, characterized in that: The brine waste liquid is selected from mining brine waste liquid, and its lithium content is 500 mg / L.

9. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 5, characterized in that: The brine waste liquid analysis solution is first placed in an oven at 85° C. for evaporation and concentration, and subsequent treatment is performed when the volume of the lithium-rich solution is concentrated 35 times.

10. A method for extracting lithium from vacuum salt production mother liquor as claimed in claim 6, characterized in that: In the nanofiltration membrane separation, the membrane pressure of the nanofiltration membrane is 2MPa, the feed liquid temperature is 25°C, and the flux is 60L / h. In the reverse osmosis concentration, the reverse osmosis membrane core flux is 60L / h, and the concentration ratio is 12.